Knockdown of miR-135a-5p Promotes Mitophagy by Regulating FoxO1/PINK1/Parkin Signaling in Hepatoma Cells Exposed to Oxidative Stress - Zhenchang, Wang; Wenfu, Zhang; Shanshan, Wu; Lei, Yang (Current Proteomics, 2023)
Introduction: Excessive oxidative stress is always associated with hepatic disease, including hepatitis, liver fibrosis, and hepatocellular carcinoma (HCC). Despite this, the intricate molecular processes driving hepatocyte apoptosis due to oxidative stress remain incompletely comprehended.Aim: Consequently, we aimed to explore the role of miR-135a-5p in hepatoma cells (HepG2/3B).Method: The assessment of protein expression was conducted through western blotting. Furthermore, miR-135a-5p expression was evaluated through RT-qPCR, and apoptosis detection was performed using a flow cytometry assay.Result: The findings suggest a connection between miR-135a-5p and mitochondrial-driven apoptosis through caspase signaling pathways. Furthermore, miR-135a-5p suppression inhibited the apoptotic response triggered by H2O2, reactive oxygen species (ROS) generation, as well as the decrease in mitochondrial membrane potential.Conclusion: Additionally, miR-135a-5p knockdown promoted mitophagy by regulating FoxO1/PINK1/Parkin signaling via targeting FoxO1. To conclude, our study implied that miR- 135a-5p might function as a probable regulator that protects cells against oxidative stress.
Keywords: HCC